Desain Aplikasi LANTAS Aplikasi Pelaporan Kecelakaan Lalulintas Berbasis Mobile - I Gede Rizki Heriana Prayoga; Ida Bagus Gede Dwidasmara (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2024)
Accidents in Indonesia are increasing every day. Based on data from the Central Statistics Agency, the range from 2019 to 2021 shows that there were 320,084 accidents in which 74,466 people died, 33,779 people suffered serious injuries, 368,773 people suffered minor injuries, and resulted in material losses of Rp. 699,888,000,000.00 due to traffic accidents on the highway. This study aims to help reduce the death toll and also traffic accident reporting by utilizing the daily use of cellphones and smart gadgets. To overcome this problem, the authors created a design solution using the prototyping method which was implemented in a mobile application. In the prototype, the user can make an emergency call to call an ambulance so that the victim can quickly get help, and also the user can easily report a traffic accident. Hopefully the design of this application can reduce victims due to traffic accident incidents.